Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1039/d1nj03697a
|View full text |Cite
|
Sign up to set email alerts
|

Selective nanomolar electrochemical detection of serotonin, dopamine and tryptophan using TiO2/RGO/CPE – influence of reducing agents

Abstract: TiO2/RGO nanocomposites were synthesised via a simple one-pot hydrothermal method and used as a modifier in carbon paste electrode for the sensitive determination of serotonin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…A slope value of −49 mV/pH implies that an equal number was near a theoretical value of −59 mV/pH, respectively . According to theoretical eq normald E normalp / normald normalp normalH = prefix− 2.303 m R T / n F where m is the number of protons and n is the number of electrons involved, the value of m / n was obtained to be 1 from the slope of the relationship of E p –pH (49.3 mV per pH unit). , This result showed that two-electron- and two-proton-transfer reactions are involved in the serotonin oxidation process. As can be seen in Scheme , the oxidation mechanism of serotonin involvement of proton and electron changes at the P-WO 3 /GCE.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…A slope value of −49 mV/pH implies that an equal number was near a theoretical value of −59 mV/pH, respectively . According to theoretical eq normald E normalp / normald normalp normalH = prefix− 2.303 m R T / n F where m is the number of protons and n is the number of electrons involved, the value of m / n was obtained to be 1 from the slope of the relationship of E p –pH (49.3 mV per pH unit). , This result showed that two-electron- and two-proton-transfer reactions are involved in the serotonin oxidation process. As can be seen in Scheme , the oxidation mechanism of serotonin involvement of proton and electron changes at the P-WO 3 /GCE.…”
Section: Resultsmentioning
confidence: 87%
“…where m is the number of protons and n is the number of electrons involved, the value of m/n was obtained to be 1 from the slope of the relationship of E p −pH (49.3 mV per pH unit). 58,59 This result showed that two-electron-and twoproton-transfer reactions are involved in the serotonin oxidation process. As can be seen in Scheme 2, the oxidation mechanism of serotonin involvement of proton and electron changes at the P-WO 3 /GCE.…”
Section: Plausible Electrochemical Reaction Mechanism Of Serotoninmentioning
confidence: 87%
“…Also, sensors such as a TiO 2 /reduced GO modified carbon paste electrode and a GO/TiO 2 /GCE, which possess a nanomolar limit of detection have also been reported. [187,188] As the electrical conductivity of reduced GO is ~600 times higher than that of GO, it is expected that the conductivity of a TiO 2 /reduced GO/ carbon paste electrode will be higher than that of a GO/TiO 2 / GCE. [189] Therefore, the difference between the limit of detection of DA at TiO 2 /reduced GO/carbon paste electrode (0.2 nM) and GO/TiO 2 /GCE (22 nM) is attributed to the difference in the electronic conductivity of reduced GO and GO in the corresponding sensors.…”
Section: Tio 2 Np-modified Sensors For Monoamine Neurotransmitter Det...mentioning
confidence: 99%
“…Consequently, a lower limit of detection was obtained at Mn 2 O 3 −TiO 2 /graphene/GCE relative to that at CuCrO 2 −TiO 2 /screen‐printed carbon electrode. Also, sensors such as a TiO 2 /reduced GO modified carbon paste electrode and a GO/TiO 2 /GCE, which possess a nanomolar limit of detection have also been reported [187,188] . As the electrical conductivity of reduced GO is ~600 times higher than that of GO, it is expected that the conductivity of a TiO 2 /reduced GO/carbon paste electrode will be higher than that of a GO/TiO 2 /GCE [189] .…”
Section: Tio2 Np‐modified Sensors For Monoamine Neurotransmitter Dete...mentioning
confidence: 99%
“…The normal human serum 5-HT levels are found to be 0.60 µM-2.00 µM. 16 People with lower 5-HT levels are more likely to have MDD, impulsivity, and suicidal behaviors. 17 For now, selective serotonin reuptake inhibitors (SSRIs) are the main antidepressant drugs.…”
Section: Introductionmentioning
confidence: 99%